Lifetime estimation of IGBT modules for MMC-HVDC application. (March 2018) - Wang, Longjun; Xu, Jiayou; Wang, Gang; Zhang, Zheng
Abstract: Modular multilevel converters (MMCs) usually work in harsh operating environments due to their compact layouts and adverse mission profiles, which accelerate the thermomechanical fatigue process in insulated-gate bipolar transistor modules (IGBTs). Accurate lifetime estimation is desired to conduct reliability prediction and develop maintenance policies. This paper presents an analytical approach to estimating the lifetimes of IGBTs for MMC-HVDC application based on the thermal cycles, which are influenced by the transmission power profile and ambient temperature profile. The structure and operating principle of MMCs are studied to develop an analytical model for computing the IGBT power loss. A thermal equivalent network in the form of a Foster model is adopted to link the power losses and junction temperature. Next, an RC equivalent circuit analytical method for characterizing the fundamental-frequency thermal cycles, developed using electrothermal analogy theory, is proposed. The rainflow counting algorithm is applied to extract the low-frequency thermal cycles from the annual junction temperature data computed at every minute. The Bayerer model is employed to predict the IGBTs lifetime. Finally, the lifetime distribution, mission profiles and comparison of different IGBTs are analyzed via case studies. Highlights: Comparing the reliability differences between IGBTs of MMC on both the rectifier side and the inverter side Analytic derivation of the fundamental-frequency thermal cycle loading on IGBTs and its effect on lifetime Introducing a junction temperature feedback to revise the lifetime under a specific ambient temperature profile